Some theoretical effects that occur within a legal system as a result of the incorporation of Human Rights Treaties to the constitutional block - Silva Abbott, Max (Derecho Público Iberoamericano, 2021)
This paper analyzes theoretically and from the perspective of International Human Rights Law, some of the consequences that occur within a national legal system, in particular for the work of its main operators, especially judges, as a result of the incorporation of human rights treaties to the so-called constitutionality block. This, thanks to the application of the “pro homine principle”, of the ideas of “minimum standard” and “compliant interpretation”, typical of international law, as well as the doctrine of conventionality control, which is fully compatible with said incorporation.